A Nation in crisis; Tigil putukan; Manhid [videorecording] - U. P. Tropa Experimental Theater Company (Quezon City Probe Production, 1991)
The first part deals with the Philippines facing a constitutional crisis over the U. S. bases treaty rejection; Second, the NPA offering a ceasefire in view of the bases treaty rejection; Third is a play entitled Manhid staged by the U. P. Tropa Experimental Theater Company.
A nation in crisis (15 min.) -- Tigil putukan (15 min.) -- Manhid (15 min.)
VHS.
Keywords: Miltary base closures -- Philippines; Military basesd, American -- Philippines; Armistices; Experimental theater